Wawasan Al-Qur'an Tentang Kesehatan Fisik dan Mental: Kajian Tafsir Mawḍu'ī - Ridwan, Ridwan; Achmad Abubakar,; Aisyah Arsyad, (Tasamuh: Jurnal Studi Islam, 2024)
This research aims to describe mawḍu'ī (contextual) interpretations of Al-Qur'an verses related to health. The type of research used is library research, using descriptive-analytical methods, with a mawḍū'ī interpretation approach. The research results show that the Al-Qur'an provides an in-depth view of the concept of health, including the concepts of physical, mental and spiritual health. In the context of physical health, several verses in the Qur'an teach about physical health, including teachings about regulating diet, adequate rest and cleanliness. Meanwhile, in the context of mental and spiritual health, several verses in the Qur'an teach about mental health, including teachings about remembrance. In regulating diet, Allah, the Most Wise, has permitted many foods and drinks, while He has prohibited only a few. This is a manifestation of His mercy and compassion towards His servants.